Increment-threshold spectral sensitivity in blindsight. Evidence for colour opponency. - Stoerig, P; Cowey, A (1991)
In the circumscribed visual field defects of 3 patients, increment-threshold spectral sensitivity was measured with a guessing paradigm. Nine 116', 200 ms narrowband stimuli with maximum transmission between 450 and 660 nm were presented on a white background of photopic or scotopic luminance. Sensitivity measured in the blind field was compared with that at matched positions in the patients' normal hemifield, and with that at corresponding positions in 2 control subjects. Results show that spectral sensitivity in the blind field, albeit reduced by up to 1 log unit, shows normal dependence on adaptation level, reflecting rod activity under scotopic, and cone activity under photopic conditions. Characteristic discontinuities in the spectral sensitivity curve seen under light adaptation are evidence for colour-opponent processes, presumably involving primate beta retinal ganglion cells.